# Welcome to $\mathsf{Pr} \infty \mathsf{fWiki}$ ProofWiki is an online compendium of mathematical proofs! Our goal is the collection, collaboration and classification of mathematical proofs. If you are interested in helping create an online resource for math proofs feel free to register for an account. Thanks and enjoy! If you have any questions, comments, or suggestions please post on the discussion page, or contact one of the administrators. Also, feel free to take a look at the frequently asked questions because you may not be the first with your idea. To see what's currently happening in the community, visit the community portal.
18,565 Proofs 14,513 Definitions Help

# Featured Proof

## Theorem

Consider the cardioid $C$ embedded in a polar plane given by its polar equation:

$r = 2 a \paren {1 + \cos \theta}$

The length of the perimeter of $C$ is $16 a$.

## Proof

Let $\mathcal L$ denote the length of the perimeter of $C$.

The boundary of the $C$ is traced out where $-\pi \le \theta \le \pi$.

$\displaystyle \mathcal L = \int_{\theta \mathop = -\pi}^{\theta \mathop = \pi} \sqrt {\paren {\frac {\d x} {\d \theta} }^2 + \paren {\frac {\d y} {\d \theta} }^2} \rd \theta$

where, from Equation of Cardioid:

$\begin {cases} x & = 2 a \cos \theta \paren {1 + \cos \theta} \\ y & = 2 a \sin \theta \paren {1 + \cos \theta} \end {cases}$

We have:

 $\displaystyle \frac {\d x} {\d \theta}$ $=$ $\displaystyle 2 a \map {\frac \d {\d \theta} } {\cos \theta + \cos^2 \theta}$ rearranging $\displaystyle$ $=$ $\displaystyle -2 a \paren {\sin \theta + 2 \cos \theta \sin \theta}$ Derivative of Cosine Function, Chain Rule $\displaystyle$ $=$ $\displaystyle -2 a \paren {\sin \theta + \sin 2 \theta}$ Double Angle Formula for Sine $\displaystyle \frac {\d y} {\d \theta}$ $=$ $\displaystyle 2 a \map {\frac \d {\d \theta} } {\sin \theta + \sin \theta \cos \theta}$ $\displaystyle$ $=$ $\displaystyle 2 a \paren {\cos \theta + \cos^2 \theta - \sin^2 \theta}$ Derivative of Sine Function, Product Rule $\displaystyle$ $=$ $\displaystyle 2 a \paren {\cos \theta + \cos 2 \theta}$ Double Angle Formula for Cosine

Thus:

 $\displaystyle \sqrt {\paren {\frac {\d x} {\d \theta} }^2 + \paren {\frac {\d y} {\d \theta} }^2}$ $=$ $\displaystyle \sqrt {4 a^2 \paren {\paren {\sin \theta + \sin 2 \theta}^2 + \paren {\cos \theta + \cos 2 \theta}^2} }$ $\displaystyle$ $=$ $\displaystyle 2 a \sqrt {\sin^2 \theta + 2 \sin \theta \sin 2 \theta + \sin^2 2 \theta + \cos^2 \theta + 2 \cos \theta \cos 2 \theta + \cos^2 2 \theta}$ $\displaystyle$ $=$ $\displaystyle 2 a \sqrt {2 + 2 \sin \theta \sin 2 \theta + 2 \cos \theta \cos 2 \theta}$ Sum of Squares of Sine and Cosine in $2$ instances $\displaystyle$ $=$ $\displaystyle 2 a \sqrt {2 + 2 \sin \theta \paren {2 \sin \theta \cos \theta} + 2 \cos \theta \paren {\cos^2 \theta - \sin^2 \theta} }$ Double Angle Formulas $\displaystyle$ $=$ $\displaystyle 2 a \sqrt {2 + 4 \sin^2 \theta \cos \theta + 2 \cos^3 \theta - 2 \sin^2 \theta \cos \theta}$ $\displaystyle$ $=$ $\displaystyle 2 a \sqrt {2 + 2 \sin^2 \theta \cos \theta + 2 \cos^3 \theta}$ $\displaystyle$ $=$ $\displaystyle 2 a \sqrt {2 + 2 \cos \theta \paren {\sin^2 \theta + \cos^2 \theta} }$ $\displaystyle$ $=$ $\displaystyle 4 a \sqrt {\dfrac {1 + \cos \theta} 2}$ Sum of Squares of Sine and Cosine and extracting factor $(1):\quad$ $\displaystyle$ $=$ $\displaystyle 4 a \cos \dfrac \theta 2$ Half Angle Formula for Cosine

 $\displaystyle \mathcal L$ $=$ $\displaystyle \int_{\theta \mathop = -\pi}^{\theta \mathop = \pi} \sqrt {\paren {\frac {\d x} {\d \theta} }^2 + \paren {\frac {\d y} {\d \theta} }^2} \rd \theta$ Area between Radii and Curve in Polar Coordinates $\displaystyle$ $=$ $\displaystyle \int_{-\pi}^\pi 4 a \cos \dfrac \theta 2 \rd \theta$ from $(1)$ $\displaystyle$ $=$ $\displaystyle 4 a \intlimits {2 \sin \dfrac \theta 2} {-\pi} \pi$ Primitive of $\cos a x$ $\displaystyle$ $=$ $\displaystyle 8 a \paren {\sin \dfrac \pi 2 - \sin \dfrac {-\pi} 2}$ evaluation between $-\pi$ and $\pi$ $\displaystyle$ $=$ $\displaystyle 8 a \paren {1 - \paren {-1} }$ Sine of Right Angle, Sine Function is Odd $\displaystyle$ $=$ $\displaystyle 16 a$

$\blacksquare$